Symbiotic Fungus Affected the Asian Citrus Psyllid (ACP) Resistance to Imidacloprid and Thiamethoxam - Yi, Tuyong; Lei, Ling; He, Ling; Yi, Jianglan; Li, Lingguo; Dai, Liangying; Hong, Yanyun (Frontiers in Microbiology, 2020)
Abstract: The Asian citrus psyllid (ACP), Diaphorina citri (Kuwayama) (Hemiptera: Liviidae), is a notorious Rutaceae plant pest. Frequent and extensive use of pesticides has resulted in severe insecticide resistance in ACP populations. Fully understanding the mechanism of ACP resistance to pesticides is vital for us to control or delay the development of resistance. Therefore, we compared the difference in resistance to imidacloprid and thiamethoxam between Hunan (Yongzhou, Chenzhou) and Guangdong (Guangzhou) ACP populations and analyzed the correlations between the resistance level and genes and symbiotic fungi. The results showed that the resistance of the Guangdong ACP population to imidacloprid and thiamethoxam was the lower than that of Hunan ACP population, and the relative expression of genes associated with P450 monooxygenase and Acetylcholinesterase was significantly the lower in the Guangdong ACP population than in Hunan ACP population. The difference of mean relative abundances of four symbiotic bacteria among three populations were marginally significant; however, the mean relative abundance of 16 fungi among three populations were significant difference, and positive linear correlations were observed between the resistance level and two fungi (Aspergillus niger and Aureobasidium pullulans) and two genes (CYP4C70 and CYP4DB1). Negative correlations were only observed between the resistance level and two fungi (Golubevia pallescens and Acremonium sclerotigenum). Moreover, four fungi were unique to the Chenzhou population which was the highest resistance to imidacloprid and thiamethoxam. These findings suggested the P450 monooxygenase and symbiotic fungi together affected ACP resistance to imidacloprid and thiamethoxam. In the future, we may use environmental G. pallescens and A. sclerotigenum to control or delay ACP resistance.